Эволюционный аспект вопросов технического моделирования конечностей млекопитающих - Манзий, С.Ф. (Вестник зоологии, 1971)
Studying the principles of structure and functioning of mammalian limbs from the bionic point of view with application of mechanics laws and methods of quantitative analysis the author and his co-workers showed that high passing ability, lightness, strength and reliability of limbs as well as economical expenditure of muscular energy are based on the principle of redundancy of a number of components, degrees of freedom in their mutual displacement and control information. It was established that this redundancy in the evolution process of terrestrial quadrupeds at first grew — up to the formation of initiai plantigradation, and in the process of specialization of limbs — decreased. In particular, it is shown that «cross-country ability» of quadrupeds depends on the redundancy of autopodium characteristics, lightness and strength of limbs — on anisotropy of bone substance, reliability — on the system of joint sebum, and economy of energy — on the lengths of links and size of angles of limb joints.